Technological Aspects of Training Future Social Pedagogues to Professional Activity - Majboroda, Galina (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
Analyzes the technological aspects of training future social pedagogues to professional activity. Analyzed the principles, proposed set of forms, methods, techniques and tools of technological training following professionals in higher education. The need for systematic technological training on such stages is identified: the formation of knowledge and skills, the formation of emotionally-valuable relation to the training process, mastery of technological knowledge, the formation of technological knowledge, skills, mastering technological expertise, creativity development, implementation process in independent professional activity training